ВЫПОЛНЕНИЕ ЗАДАЧ И УПРАЖНЕНИЙ КАК ЭФФЕКТИВНОЕ СРЕДСТВО ИЗУЧЕНИЯ ЭКОЛОГИИ - Ажиева, М.Б. (SCIENCE and SOCIETY, 2016)
In the given article there are offered various forms of the tasks of different degree of difficulties in the course "Bases of ecology". The teachers will be able to select all the necessary didactic material for the individual tasks and for tests during the lesson. To tasks and problems are given the detailed answers that will allow the students to use the given material both for self-control, and for increasing preparation level and systematization of the knowledge.